Pelvic artery embolisation for severe post partum haemorrhage in a tertiary care centre in the UK. (7th June 2011) - Ruprai, C K; Jha, R; Robinson, G; Kanwar, S
Abstract : This study aims to determine the effectiveness of pelvic artery embolisation in 18 cases of severe post partum haemorrhage that occurred over a period of 7 years. The setting was based in a university affiliated tertiary referral centre in Hull. Over the 7 year period there were 42 000 deliveries of which 70% were normal, 23% caesareans and 7% delivered by vaginal assistance. 1111 deliveries were complicated by postpartum haemorrhage. All women had primary post partum haemorrhage and received conventional treatment as per our local and RCOG guidelines. 18 of these patients underwent embolisation because of failure of conservative measure. They were transferred from labour ward to the 24 h access interventional radiology suite located within the hospital once they were haemodynamically stable. The radiology suite was equipped with a high speed digital angiography system. Embolisation was performed using gelfoam. The diagnosis of uterine atony was made in 78% of cases before embolisation and four patients had abnormal placental implantation. 4 out of the 18 patients underwent peripartum hysterectomy. The mean time between decision to embolise to transfer to the radiology suite was 7 min. The mean duration of the procedure was 45 min. Embolistion was successful in 78% of patients. 50% of unsuccess had bilateral iliac arteries embolised. The average blood loss was 3.7 l. All patients had an uneventful recovery and one subsequently had a successful pregnancy. Conclusion: Selective artery embolisation is safe and effective with limited or no morbidity as an alternative to classic haemostatic surgery.